Impact of institutional quality on foreign capital invested in Africa - (:unkn) unknown (My University, 2024)
This paper analyses the short-and long-term impact of institutional quality on FDI inflows in 31 African middle-income countries over the period 2002-2022 using the ARDL method with PMG. We constructed a synthetic index of institutional quality using the principal component analysis method in order to best reproduce the variance of the six kaufman-kray governance indicators. The results show that, in the short term, institutional quality has no effect on FDI inflows, unlike the economic environment, which has an effect in both the short and long term. On the other hand, institutional quality plays a key role in attracting foreign capital in the long term, more so than the economic environment. In fact, a one-percentage point increase in 'institutional quality' generates a 1,068% increase in 'FDI flows'. However, the results of the individual effect of the six governance indicators reveal the importance of these indicators, with a significant and positive coefficient, except for the 'capacity to make demands and express oneself' indicator, which has a negative effect.
Keywords: African Research